PENGARUH GAYA BELAJAR DAN KECERDASAN MAJEMUK TERHADAP PRESTASI BELAJAR SANTRI: Penelitian pada Santri Riyadlul Huda Sukaguru Singaparna Tasikmalaya - Syarif Hidayat; Nurjanah (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2022)
Learning style is a cognitive, affective and psychomotor characteristic that can stabilize students in the process. A person's learning style is very diverse. By knowing learning styles from the start, students can develop all their intelligence potential, including logical-mathematical, linguistic, naturalist, physical-kinesthetic, visual-spatial, musical, interpersonal and intrapersonal intelligence. Therefore, the learning style and multiple intelligences can affect one's learning achievement. The author in this case conducted research at the Riyadlul Huda Sukaguru Islamic Boarding School, Singaparna, Tasikmalaya. This research is a correlational research that is survey in nature and takes a sample of 100 respondents. The data sources were obtained directly from the leadership, administrators and students with quantified qualitative data. Data collection techniques are carried out by: (1) Partial correlation coefficient analysis; (2) Multiple correlation coefficient analysis; (3) Analysis of the coefficient of determination; (4) t and F test; (5) Regression analysis. The results of the study prove: 1) There is a positive influence between learning styles and student achievement as seen from the b1 coefficient of +0.537 with a significant value of tcount of 0.000. It means that the significant value of tcount is 0.000 for b1 which is lower than significant alpha = 0.05. 2) A positive influence was found between multiple intelligences and student achievement as seen from the b1 coefficient of +0.561 with a significant value of tcount of 0.000. It means that the significant value of tcount is 0.000 for b1 which is lower than significant alpha = 0.05. 3) A positive influence was found between learning styles and multiple intelligences on student achievement as seen from the coefficient b1 of +0.349 and b2 of +0.343 with a significant value of tcount (b1) of 0.000 and a significant value of tcount (b2) of 0.001. It means that the significant value of tcount (b1) is 0.000 and the significant value of tcount (b2) is 0.001 which is smaller than significant alpha = 0.05.